“Das trevas da ignorância para alcançar a luz divina do saber”: educação, religião e política na trajetória de Albertino Marques Barrêto (Brumado, 1954-1974) - Lima, Rui Marcos Moura (2016)
The purpose of this paper is to analyze the trajectory of Albertino Marques Barrêto in the city of Brumado, in southwestern Bahia. The time frame for this work begins in 1954 when Albertino and a group of “brothers” founded the Spiritual Center Fellowship (CEF) and ends in 1974, when not only can we envision his role in the “religious field,” but also as a politician during his participation in the founding of the Union of Rural Works of Brumado. This paper also endeavors to comprehend the defense of Albertino’s disputed political project in the different political spaces in which he acted over the course of this twenty-year period. This research alos uncovers that Albertino’s activity was always based on ideas of spiritualism, including his design for education, which had the basic principle of taking the man out of “ignorance” to form a “new man.”